2008
DOI: 10.1056/nejmoa0707534
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Recombinant Activated Factor VII for Acute Intracerebral Hemorrhage

Abstract: Hemostatic therapy with rFVIIa reduced growth of the hematoma but did not improve survival or functional outcome after intracerebral hemorrhage. (ClinicalTrials.gov number, NCT00127283 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
793
5
20

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,136 publications
(835 citation statements)
references
References 23 publications
17
793
5
20
Order By: Relevance
“…These results are in accordance with the potent antihemorrhagic activity we had previously demonstrated in murine models of mild and severe bleeding 20. Moreover, reduction in hematoma expansion achieved with CM352 was accompanied by a substantial improvement in functional and neurological recovery, in marked contrast with clinical trials of rFVIIa, which reduced hematoma growth but did not improve survival or functional outcome after ICH 9. The use of the antifibrinolytic agents ε‐aminocaproic acid and TXA has been proposed after ICH (STOP‐AUST trial)11; however, the only experimental evidence available shows that TXA exacerbates edema in a mouse model of warfarin‐associated ICH 29.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in accordance with the potent antihemorrhagic activity we had previously demonstrated in murine models of mild and severe bleeding 20. Moreover, reduction in hematoma expansion achieved with CM352 was accompanied by a substantial improvement in functional and neurological recovery, in marked contrast with clinical trials of rFVIIa, which reduced hematoma growth but did not improve survival or functional outcome after ICH 9. The use of the antifibrinolytic agents ε‐aminocaproic acid and TXA has been proposed after ICH (STOP‐AUST trial)11; however, the only experimental evidence available shows that TXA exacerbates edema in a mouse model of warfarin‐associated ICH 29.…”
Section: Discussionsupporting
confidence: 90%
“…Strategies addressing hematoma expansion by lowering blood pressure,7 surgical hematoma removal,8 reversal of anticoagulants,3 or hemostatic therapy with rFVIIa9 have provided evidence of reduced hematoma growth, but results regarding long‐term therapeutic benefit have been mainly disappointing 4. Moreover, to our knowledge, only a few preclinical studies have been conducted to assess the effects of the pharmacological modulation of hematoma growth 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently published results of a phase three randomized trial including 841 patients of ICH by the same group concluded that haemostatic therapy with rFVIIa reduced growth of the haematoma but did not improve survival or functional outcome after ICH [20]. Study also showed increased risk of thromboembolism, particularly arterial, in rFVIIa treated group.…”
Section: Spontaneous Intracerebral Hemorrhage (Ich)mentioning
confidence: 99%
“…A high response rate in the placebo arm can affect the potential of detecting treatment effects in clinical trials 20, 21, 22. In the CHIMES study, almost half in the placebo group achieved functional independence (mRS 0 to 1) at the end of 3 months.…”
Section: Discussionmentioning
confidence: 99%